Kajian Fikih terhadap Praktek Gadai Emas di Pegadaian Syariah Sumbawa Perspektif Hukum Islam - Irawan, Feri; Addi Pratama, Muhammad; Mawarni, Iga; Adekantari, Sasmita (Tasyri' : Journal of Islamic Law, 2025)
This study aims to examine the practice of gold pawning in Sharia Pawnshops in Sumbawa Regency from the perspective of Islamic law. Gold pawning is a form of sharia-based financing service that is in great demand by the public. However, the implementation of this service contains a number of aspects of fiqhiyyah that need to be studied in depth, especially related to the validity of the contract, the clarity of costs, and the application of the principle of justice in accordance with sharia provisions. This research uses a qualitative approach with a descriptive-analytical method. Data was obtained through in-depth interviews with Sharia Pawnbrokers and customers, as well as literature studies on fiqh literature and regulations related to sharia pawns. The results of the study show that in general, the Sharia Pawnshop of Sumbawa Regency has implemented two types of contracts in accordance with sharia principles, namely the rahn (pawn) and ijarah (rent) contracts. However, there are still several obstacles in the field, such as the lack of public understanding of the contract mechanism used, and the lack of transparency in the imposition of administrative fees, which has the potential to cause doubts (syubhat). Based on fiqh analysis, the practice of gold pawning at Sumbawa Sharia Pawnshops can be categorized in accordance with the principles of Islamic law as long as it avoids the elements of riba and gharar, and upholds the principles of openness and justice. This study recommends increasing Islamic financial literacy for the community and strengthening information transparency by Pegadaian so that this service is more optimal and in line with Islamic legal values.